P139 The burden of copd across the european union: development of the european copd atlas. (15th November 2016) - Boven, JFM van; Gaughan, J; Soriano, JB; Correia de Sousa, J; Baxter, N; Román-Rodríguez, M; Vilaró, J; Williams, S; Fitch, S; Kishore, K; Chaudhury, H
Abstract : Background: Estimating current and future impact of chronic obstructive pulmonary disease (COPD) within the European Union (EU) is essential for targeted and well-informed policy-making, however, current global and regional estimates are contradictory, and comparable standardised data is lacking. Without it the burden felt by individuals and healthcare systems cannot be fully quantified and a collective and coordinated response cannot be achieved to protect economies and communities from further harm. Aim: Our purpose was to Collect data to enable a comparative assessment of the COPD burden across EU 28 member states and highlight variation. Show the impact of COPD in the workplace, on healthcare utilisation and on quality of life of the EU population. Use the data to underpin a simulation model to demonstrate future impact on societies, health inequalities and healthcare utilisation depending on which interventions are selected. Methods: A systematic literature review was performed to identify regional and national data on COPD prevalence, risk factors (e.g. smoking, air pollution), impact and costs across the EU. Workshops with stakeholders from a range of European countries were convened to test the face validity of the data, and to develop policy-level questions from which a simulation model could be developed. Results: Prevalence estimates of COPD varied considerably (1.26% to 13.87%), partly because of different definitions. As smoking rates are less affected by definition differences, these were used in a model that predicts COPD incidence, prevalence and mortality. Correction factors were applied to account for non-smoking related causes and under diagnosis of smoking. Smoking prevalence rates were used to estimate data for equivalent countries for the countries where smoking data were not available. The simulation model is currently in development and first results are expected in Autumn 2016. Conclusion: The European COPD Coalition (ECC) will use the results to facilitate dialogue with EU decision makers (European Commission Council and Parliament) on health policy, outlining the problem and providing evidence to support the call for political actions on COPD. It will also be of significant interest to healthcare professionals, patients, and respiratory organisations with a passion to improve COPD care